Changes in total sugar and protein content in germinating rice seeds under salinity stress - Yap, Mei Kee (2015)
Rice (Oryza sativa L.) is the main staple food for more than half of the world’s population. It is a salt sensitive species and susceptible to salinity stress condition. Some of the irrigated lands in Malaysia are salt-affected and rice grown in these areas was reported to have reduced yield. In this study, the effect of salinity on the germination of two Malaysian rice cultivars MR219-9 and MR253 was investigated. The cultivars are commercially grown in Malaysia. The rice seeds were germinated in vitro and the germination capacity was observed for six days. The salt-stressed seeds were treated with 150mM NaCl and the control did not contain NaCl. The germinated seeds were analysed for soluble sugar and protein content. The results showed that the presence of 150mM NaCl caused significant reduction in all the growth parameters measured as well as the soluble sugar and protein content for both cultivars. For MR219-9, the 150mM NaCl decreased the percentage of germination by 22.5% and reduced the rate of germination by 68.31%. The plumule length was decreased by 66.99% and the radicle length by 56.66%. Similarly, the soluble sugar and protein content of the germinating seeds were drastically reduced. A similar trend was observed for MR253 cultivar, however the effects were not as severe as compared to MR219-9. Thus, it was concluded that salinity stress significantly affected the seed germination and reduced the soluble sugar and protein content of two Malaysian rice cultivars MR219-9 and MR253.